Pemanfaatan Air Limbah Hasil Pengolahan IPAL Komunal Sebagai Water Scrubber Pabrik II Industri Pupuk PT X - Naura Alfi Amelia; Praditya Sigit Ardisty Sitogasa (Environmental Engineering Journal ITATS, 2026)
The fertilizer industry PT X produces liquid waste from various production processes that have the potential to pollute the environment if not managed properly. This study aims to examine the performance of utilizing treated water from the communal Wastewater Treatment Plant (WWTP) as a water scrubber medium in controlling gas emissions at Plant Unit II. The research method is descriptive with an observational approach through field observations, interviews, and analysis of WWTP operational data and emission quality test results. The results show that treated water from the communal WWTP can be utilized effectively without reducing emission control performance. The particulate concentration in the scrubber stack was recorded at around 9-10% of the quality standard, while the fluorine and ammonia concentrations were in the range of 29-69% and 7-11% of the quality standard of LHK Regulation Number 17 of 2019, respectively. The utilization of treated water reached 25–32% of the communal wastewater treatment plant discharge, thereby contributing to reducing the use of clean water. The water remaining from the water scrubber process is returned to the communal wastewater treatment plant for reprocessing, forming a recirculation system that increases resource efficiency, reduces liquid waste, and supports air pollution control. The novelty of this research lies in the assessment of the integration of treated water from communal wastewater treatment plants into water scrubber systems as a unified approach to wastewater management and emission control in the fertilizer industry in Indonesia, this reflects the application of the principles of zero waste, clean production, and circular economy in supporting environmental sustainability and company performance in the Program Penilaian Peringkat Kinerja Perusahaan (PROPER).